Monitoring Restaurant Taxes Through the Use of Tapping Box Tools - Arizah, Ainun; Abdi, Muhammad Nur; Adil, Muhammad; Elfhita, Resky Vivi (Contemporary Journal on Business and Accounting, 2025)
Purpose – This study aims to determine the implementation of restaurant tax monitoring through the use of tapping box tools at the Regional Revenue Agency of Mamuju Regency. Design/methodology/approach – This study uses a qualitative research method by focusing on the implementation of restaurant tax monitoring through the use of a tapping box tool. Findings – The results of the study show that, 1) the implementation of monitoring carried out by BAPENDA on restaurant taxes by installing tapping boxes in restaurants is then checked on the SIMPADA application which can be accessed via https://sulselbar.simpada.co.id/sulselbar-taxmonitoring/, 2) The limited number of human resources means that they have to work outside their normal working hours and is not followed by an increase in the amount of salary or wages received. Originality - This research lies in an in-depth study of the application of the Tapping Box Tool by linking it to technical and non-technical aspects. Keywords: Monitoring, Restaurant Tax, Tapping Box Paper type Research Result